The Waste Land: Deconstructing Spiritual Philosophy (AMC Journal (Dhangadhi), 2025)
This paper explores how philosophy is transformed from its original state with time. T. S. Eliot’s poem, The Waste Land (1922) is taken as a primary text to explore the changing meanings of philosophy of established norms. Deconstruction is a theory inaugurated by Jacques Derrida in the late 1960s and became a major influence on literary studies during the late 1970s. Tyson (2006) says, “…according to Derrida, language is not the reliable tool of communication we believe it to be, but rather a fluid, ambiguous domain of experience in which ideologies program us without being aware of them (p. 249).” Since deconstruction sees the multiplicity and contradictions of meanings in the text rather than a single pre-established meanings, The Waste Land incompasses a number of such instances. “Meaning is created by the reader in the act of reading (Tyson: 2006, p. 258).” Therefore, the poem is successful and rich in bringing the fragmentations in the existing philosophy in the contemporary modern world. The poet brings the various references from different spheres of life such as mythology, art, literature, music etc. and each reference is deviated from its classical spirit. For instance, water, sex, human values, morality in profession have been found in different forms than they used to be. Water was the symbol of survival, but now it is the means of death. Similarly, sex is found deviated from its fundamental rhythm and it is now limited to physicality without any touch of spirituality. The poem contains the elements like fragmentations, meaninglessness, and gloom of the contemporary world which are clearly visible for deconstructing the pre-established philosophy.